Wetland plant species improve performance when inoculated with arbuscular mycorrhizal fungi: a meta-analysis of experimental pot studies - Ramírez-Viga, Thai Khan (2018)
The presence of arbuscular mycorrhizal fungi (AMF) inwetlands is widespread. Wetlands are transition ecosystems between aquatic andterrestrial systems, where shallow water stands or moves over the land surface.The presence of AMF in wetlands, suggests that they are ecologicallysignificant, however, their function is not yet clearly understood. With theaim of determining the overall magnitude and direction of AMF effect on wetlandplants associated with them in pot assays, we conducted a meta-analysis of dataextracted from 48 published studies. The AMF effect on their wetland hosts wasestimated through different plant attributes reported in the studies includingnutrient acquisition, photosynthetic activity, biomass production and salinestress reduction. As the common metric, we calculated the standardized unbiasedmean difference (Hedges´d) of wetlandplant performance attributes in AMF-inoculated plants versus non-AMF-inoculatedplants. Also, we examined a series of moderator variables regarding symbiontidentity and experimental procedures that could influence the magnitude anddirection of an AMF effect. Response patterns indicate that wetland plantssignificantly benefit from their association with AMF, even under floodedconditions. The beneficial AMF effect differed in magnitude depending on theplant attribute selected to estimate it in the published studies. The nature ofthese benefits depends on the identity of the host plant, phosphorus additionand water availability in the soil where both symbionts develop. Ourmeta-analysis synthetizes the relationship of AMF with wetland plants in potassays and suggest that AMF may be of comparable importance to wetland plantsas to terrestrial plants.